2017
DOI: 10.1515/pjfns-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Treatments with Methyl Jasmonate and Salicylic Acid for Maintaining Physico-Chemical Characteristics and Sensory Quality Properties of Apricot Fruit during Cold Storage and Shelf-Life

Abstract: The aim of this study was to investigate the effect of methyl jasmonate and salicylic acid on 12 quality parameters of apricot fruit in treatments of cold storage (1 o C for 7, 14 and 21 days) and shelf-life (4 and 8 days at 25 o C after a 21-day cold storage treatment). Fruit quality parameters included 6 physico-chemical characteristics (weight loss, fruit fi rmness, total soluble solids, acidity, total soluble solids/acidity ratio and juice pH) and 6 sensory properties (skin and fl esh colour, texture, tast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 20 publications
5
36
1
Order By: Relevance
“…During cold storage, applications of T 8 and T 9 were more effective in reducing this character in both seasons. Our results are in agreement with those of Babalar et al (2007) on strawberry and Ezzat et al (2017) on apricot, they concluded that, polyamines applications were effective delaying maturity and fruits ripening.…”
Section: E Ssc/acid Ratiosupporting
confidence: 92%
“…During cold storage, applications of T 8 and T 9 were more effective in reducing this character in both seasons. Our results are in agreement with those of Babalar et al (2007) on strawberry and Ezzat et al (2017) on apricot, they concluded that, polyamines applications were effective delaying maturity and fruits ripening.…”
Section: E Ssc/acid Ratiosupporting
confidence: 92%
“…Chemical or physical disinfection of fruits encounters lack of consumer acceptance, low efficiency, and high‐associated cost (Lacombe et al., 2015; Pinela & Ferreira, 2017). Therefore, development of effective removal of microbial contamination from the fresh products is vitally important (Ezzat et al., 2017; Fridman et al., 2007). Heat sterilization, as a conventional method to disable or destroy pathogens, is not suitable for many fruits and vegetables, and causes unwanted side effects on the taste and nutritional value of the product (Afshari & Hosseini, 2013; Hou et al., 2019; Pinela & Ferreira, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Salicylic acid (SA), chemically known as two hydroxy benzoic acid is one of a diverse group of phenolic compounds. Studies have demonstrated that SA acts as a signaling molecule; regulates respiration, senescence‐associated gene expression, and enzymatic activities; controls diseases and extend the storage life of fruits 6–9 . SA also exhibits antagonistic effects on both ethylene biosynthesis and ethylene action 10 .…”
Section: Introductionmentioning
confidence: 99%